A fluid model for the simulation of fluid‐structure interaction in the Scaled Boundary Finite Element Method for prismatic structures. Issue 1 (17th December 2018) - Wasmer, Paul; Krome, Fabian; Bulling, Jannis; Prager, Jens
Abstract: The Scaled Boundary Finite Element Method is known as an efficient method for the simulation of ultrasonic wave propagation. As to investigate acoustic wave behavior in case of fluid‐structure interaction, a fluid model is implemented in the SBFEM for prismatic structures. To omit coupling terms a displacement‐based formulation is used. Spurious modes, which occur in the solution, are suppressed using a penalty parameter. To verify this formulation dispersion curves obtained with Comsol Multiphysics are compared to results of SBFEM. The results of both methods are in very good agreement.